Le régime primaire dans le nouveau Code civil du Québec : quelques remarques critiques - Caparros, Ernest (Les Cahiers de droit, 1981)
The author points out, in the introduction, that the reform introduced by Bill 89 is limited to one of the nine Books that the new Civil Code of Québec will have, and that even in this Second Book only 151 articles are in force. He then studies the contribution of the spouses to the needs of the family as regulated by the new provisions: the mutual obligation to contribute is now imposed by law. The autor regrets that the new Code restricts the concept of contribution in the form of work to household work. He underlines that the solidarité aimed at by the new provisions may be jeopardized by the continued application of rules from the present Civil Code of Lower Canada. As for the protection of the family residence, the author indicates how this protection is in some cases very limited and questions the efficiency of the formalities required. He also regrets that the new provisions concerning the fate of the family residence at the end of the cohabitation have not been put in force yet. Finally, he criticizes the provisions concerning judicial intervention in family matters.